Spinal dural arteriovenous fistulas – presentation, management and outcome in a single neurosurgical institution. (August 2013) - Clark, S.; Powell, G.; Kandasamy, J.; Lee, M.; Nahser, H.; Pigott, T.
Abstract: Objective . To compare the outcome, with respect to treatment modality, of patients treated with spinal dural arteriovenous fistulas (SDAVF). Method. Retrospective cohort study of patients with SDAVF assessed at a single tertiary referral centre, between 1999 and 2009. Intervention type, pre-/ post-intervention Aminoff–Logue disability score (ALDS) and recurrence rate were obtained from medical records. Results . 26 patients were identified with 23 receiving intervention. All patients initially received super selective angiogram, with 13 undergoing endovascular embolization at this stage, after discussion between the surgeon and interventional radiologist. Six patients who underwent embolization had a recurrence. The remaining 10 patients had fistulas marked during angiography, and were then treated surgically, after discussion. One of these recurred. The difference in recurrence rate between the two intervention types was not statistically significant. Fistulas treated with the embolization material onyx were twice as likely to recur as those treated with the alternative material, histoacryl–lipiodol. There was a statistically significant difference between the modes of intervention in relation to clinical outcome. Surgeries lead to an improvement in neurology, whereas treatment via embolization did not. Neurological improvement was seen in non-recurring cases, however deterioration in neurological function occurred with fistula recurrence. Conclusion . Super selective angiography is effective in defining the relevant vascular anatomy and allows for precise fistula localization during any potential subsequent surgery. Onyx was associated with a higher recurrence rate, suggesting it is less suitable as an embolization material for SDAVF treatment. Surgery appeared to correlate to reversal of neurological impairment seen at presentation, possibly due to a lower recurrence rate. The study is limited by small patient numbers, emphasizing the need for further studies of SDAVF patients.